Main aspects of reproductive health of adolescent girls and girls of early reproductive age. (Overview) - Kholova Nodira Fazliddinovna (Genius Publishing Group, 2022)
Reproductive health of teenage girls and women of young age stands out for its social and political significance. It is directly related to the health of children and, consequently, to the future of the state, the health and preservation of the gene pool of the people of our Republic of Uzbekistan.Prevention and treatment of violations of the formation of the reproductive system should be comprehensive and individual, with the participation of psychologists, teachers, general practitioners, gynecologists, carried out taking into account complaints and the quality of life of each girl.
Keywords: reproductive health; teenage girls; health maiden; young women